Legal Barriers and Quality Compliance in the Business of Biofertilizers and Biopesticides in India - Arjjumend, Hasrat; Koutouki, Konstantia (Journal of Legal Studies, 2020)
Biofertilizers and biopesticides (together known as ‘biologicals’) hold the potential to increase farmers’ current agricultural productivity, while at the same time contributing to the soil’s ability to produce more in the future. However, the legal registration of microbial products and the operation of businesses dealing in biologicals face certain barriers, which ultimately affect the expansion and widespread use of these green products in Indian agriculture. By involving manufacturers, suppliers and traders of biologicals, as well as government officers dealing with biologicals in India, a study was conducted using participatory methods of semi-structured interviews, structured interviews and informal discussions. This article explores the participants’ perceptions and understanding of the barriers, obstacles and issues in the registration, licensing, proliferation and business operations surrounding the manufacturing, sale, trade, import, export, storage, use, and transport of microbial products. Numerous barriers to business and trade in microbial green products – biofertilizers and biopesticides – are identified. Nevertheless, certain weaknesses related to quality compliance and monitoring are also identified on the part of the manufacturers and suppliers of these biologicals, indicating that the government’s regulatory system must be more efficient and competent in handling these processes.